Drinking in the shadow economy - Christopher Snowdon (Institute of Economic Affairs (IEA), 2012)
One in ten bottles or cans of beer sold in the UK have not had duty paid on them and there are growing reports of counterfeit spirits being sold by licit and illicit retailers. HMRC seized almost ten million litres of non-duty paid alcohol in 2010/11, a rise of 30 per cent in two years. The UK loses more revenue from the cross-border movement of alcohol than any other EU state. The aim of this paper is to identify the factors that encourage the production, distribution and purchasing of alcohol in the shadow economy. Unrecorded alcohol encompasses smuggled alcohol, commercially manufactured counterfeit alcohol, domestic brewing and distilling, surrogate alcohol, alcohol fraud and cross-border shopping. Failing to deal with alcohol's shadow economy threatens not only the public finances, but also public health and public order. Counterfeit spirits and surrogate alcohol frequently contain dangerous levels of methanol, isopropanol and other chemicals which cause toxic hepatitis, blindness and death. Alcohol smuggling and counterfeiting is linked to other illegal activities, including drug smuggling, prostitution, violence, money-laundering and terrorism. Factors which lead to shadow economic activity include high taxes and social security payments, low tax morale, complex tax systems, low Gross Domestic Product, weak institutions and corruption. Evidence shows that the illicit alcohol market is also closely associated with high taxes, corruption and poverty. The affordability of alcohol appears to be the key determinant behind the supply and demand for smuggled and counterfeit alcohol. Affordability is low in some countries due to low incomes (e.g. Eastern Europe) and in others because of high alcohol duty (e.g. Scandinavia). The price of alcohol in neighbouring markets also influences rates of unofficial consumption. Demand for alcohol is relatively inelastic and drinkers have a series of options available to them when real prices increase. They can do as the government hopes and drink less, but they can also do any of the following: (1) make savings elsewhere in the household budget, (2) switch from the on-trade to the off-trade, (3) downshift to cheaper drinks, (4) shop abroad, (5) brew or distil their own alcohol, (6) buy counterfeit or smuggled alcohol, and finally (7) buy surrogate alcohol (e.g. methanol, antifreeze, aftershave). The extent to which consumption patterns change depends on personal income and the affordability of alcohol. Our analysis indicates that the affordability of alcohol does not have a strong effect on how much alcohol is consumed. Once unrecorded alcohol is included in the estimates, it can be seen that countries with the least affordable alcohol have the same per capita alcohol consumption rates as those with the most affordable alcohol. Alcohol duty provides significant income to European governments, but maximising these revenues carries significant risks in terms of health, crime and secondary poverty. Lessons can be learnt from countries which have low rates of unrecorded alcohol. We conclude that economic prosperity, moderate taxation and minimal corruption are essential for a country to minimise the size the alcohol black market. Without these preconditions, efforts to tackle the illicit alcohol supply through education, deterrence and enforcement are unlikely to succeed.
Keywords: 330; Shadow economy; Alcoholic beverages; Illicit trade; Criminal policy; Great Britain; Schattenwirtschaft; Alkoholisches Getränk; Illegaler Handel; Kriminalpolitik; Großbritannien